NEUROLOGICAL PAROXYSMAL DISORDERS IN CHILDREN WITH HYPOGLYCEMIA IN CONGENITAL HYPERINSULINISM: POLYMORPHISM OF CLINICAL IMPLICATIONS - I. O. Shchederkina; M. A. Melikyan; A. N. Zavadenko; E. V. Kozlova; N. N. Zavadenko (Эпилепсия и пароксизмальные состояния)
Hypoglycemia in congenital hyperinsulinism (WGI) in children increases the risk of brain damage, seizures and development delay. The aim of our study was to evaluate the clinical manifestations in children with CHI. Hypoglycemia is often manifests with seizures, which are sometimes in the future may lead to the development of epilepsy. Seizures in CHI do not always require a diagnosis of epilepsy and prescription of anticonvulsants. EEG changes in these children may be observed in the absence of epileptic seizures. Developmental delay was more common in children with neurological abnormalities and MRI changes. Children with ABCC8 gene mutations have more complicated for CHI and more prominent developmental delay.